Techniques and strategies to imp Techniques and strategies to improve primary school students’ reading skills.: Techniques and strategies to improve primary school students’ reading skills. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
Abstract: To understand the passage being read one has to undergo the complex cognitive processes that are necessary to be embedded with reading activity to give the readers to understand the meaning of the material they are reading. At school the students usually get the main source of knowledge from texts so comprehending what they read is highly important when they move from one class to another. Practicing reading is conventionally based on teacher’s instructions and guidance by reading texts in textbooks and organizing answer-question talk on accordance with the content of the reading material. (Smagorinsky, 2001; Toste, Fuchs & Fuchs, 2013). Bu it is not enough to be an effective reader what it means that students have to develop effective reading skills that could improve their ability to access complex content delivered in textbooks to be successful in general education classrooms. The reason is that it is expected from today's youth to raise their literacy skills to higher level compared to the past generations to meet the requirements of the business environment.